Analysis of the prevalence of occupational diseases among dentists in the health sector in Trujillo - Palomino de Taboada, Gladys Isaura (2024)
Objetive: to determine the most prevalent occupational diseases among dentists in the health sector of Trujillo. Methods: The sample was made up of 80 dentists working in MINSA and EsSALUD in the province of Trujillo. It was determined by simple random probability sampling and a survey was applied. The data were analyzed in SPSSv24. Results: the occupational diseases with the highest prevalence according to age were those caused by biological agents, which affected dentists between 26 and 35 years of age (13.8%), the group between 36 and 40 years of age (41.3%) and the group between 46 and 55 years (17.5%). The age group between 56 and 65 years showed a higher prevalence of diseases caused by chemical agents (11.3%). In both the male (48.8%) and female (28.8%) sexes, the occupational diseases with the highest prevalence were those caused by biological agents in dentists with a period between 1 and 10 years of professional care (31.3%) and those with a period between 11 and 20 years (36.3%). Conclusion: The occupational diseases with the highest prevalence among dentists in the health sector in Trujillo were those caused by biological agents. They were followed by those caused by chemical agents and those caused by physical agents.